Vector field radial basis function approximation. (September 2018) - Smolik, Michal; Skala, Vaclav; Majdisova, Zuzana
Highlights: It provides mechanism to visualize vector field without excessive cluttering while maintaining global structure of the flow. We use Radial Basis Functions (RBF) approximation with Lagrange multipliers for vector field approximation. Important critical points are preserved in the approximated vector field. A significant contribution of the proposed method is an analytical form of the vector field which can be used in further processing. The algorithm proved its simplicity and ability to approximate a complex vector field. Abstract: Vector field simplification aims to reduce the complexity of the flow by removing features according to their relevance and importance. Our goal is to preserve only the important critical points in the vector field and thus simplify the vector field for the visualization purposes. We use Radial Basis Functions (RBF) approximation with Lagrange multipliers for vector field approximation. The proposed method was experimentally verified on synthetic and real weather forecast data sets. The results proved the quality of the proposed approximation method compared to other existing approaches. A significant contribution of the proposed method is an analytical form of the vector field which can be used in further processing.